2020
DOI: 10.3390/ijerph17186601
|View full text |Cite
|
Sign up to set email alerts
|

Does the Addition of Manual Therapy Approach to a Cervical Exercise Program Improve Clinical Outcomes for Patients with Chronic Neck Pain in Short- and Mid-Term? A Randomized Controlled Trial

Abstract: Chronic neck pain is one of today’s most prevalent pathologies. The International Classification of Diseases categorizes four subgroups based on patients’ associated symptoms. However, this classification does not encompass upper cervical spine dysfunction. The aim is to compare the short- and mid-term effectiveness of adding a manual therapy approach to a cervical exercise protocol in patients with chronic neck pain and upper cervical spine dysfunction. Fifty-eight subjects with chronic neck pain and upper ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 63 publications
10
29
1
4
Order By: Relevance
“…In the present study, improvement in neck disability in both manual therapy groups compared to the Control Group, reached the minimal clinically important difference. These results are comparable to those of previous studies using multimodal approaches including manual therapy and cervical exercises 28,29 and superior to studies which regional mobilization, manipulation or exercise were performed in isolation. 26,27,29,33…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, improvement in neck disability in both manual therapy groups compared to the Control Group, reached the minimal clinically important difference. These results are comparable to those of previous studies using multimodal approaches including manual therapy and cervical exercises 28,29 and superior to studies which regional mobilization, manipulation or exercise were performed in isolation. 26,27,29,33…”
Section: Discussionsupporting
confidence: 84%
“…Multimodal approach associated with specific upper cervical mobilization seems to be superior in reducing pain 27 than the application of a multimodal approach but without specific mobilization or manipulation. 27,28 Conversely, Rodríguez-Sanz et al 29 showed that adding four 20-minutes sessions of upper cervical manual therapy to an exercise program was more effective in relieving neck pain at short- and mid-term in a similar sample as in our study. Therefore, more studies are needed to analyse the optimal dosage of the upper cervical manual therapy approach.…”
Section: Discussionsupporting
confidence: 71%
“…Forty-eight primary care subjects (12 men and 36 women) were included in the study. The inclusion criteria comprised: medical diagnosis of chronic neck pain with more than three months of evolution [ 35 ], a positive result in the flexion-rotation test (less than 33° or a difference of 10° or more between the two rotations) [ 6 , 8 , 9 ] and loss of mobility in C0-1 and/or C2-3 spine segments found through manual assessment according to Zito et al and Kaltenborn [ 36 , 37 ]. Subjects were also required to be over 18 years old and sign the informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Most rotational movement of the upper cervical spine occurs at the C1-2 segment [ 3 ]. The flexion-rotation test is the most used test to assess the range of movement (ROM) in the transverse plane of the upper cervical spine, and it is a valid and reliable test [ 4 , 5 , 6 , 7 ]. This test is an easily applied method of manual examination that localizes the presence of joint dysfunction at C1-2 level [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation